Negative impact of nurses’ fear of COVID-19: the moderating role of implementation of knowledge management - Chu, Li-Chuan (Frontiers in Public Health, 2024)
Background During the COVID-19 pandemic, nurses encountered substantial infection risks and psychological strain, which severely affected their emotional well-being, professional attitudes, and job performance. This study investigated the impact of nurses’ fear of COVID-19 on their intention to leave the occupation and emotional labor as well as the moderating role of the implementation of knowledge management on these primary variables. Methods To mitigate common method bias, this research adopted a two-phase questionnaire approach, targeting nurses at a medical center in central Taiwan. In the first phase, 300 copies of questionnaire were distributed for participants to complete self-assessment surveys covering fear of COVID-19, knowledge management implementation, and demographic information. After 1 month, the participants were invited to complete a follow-up questionnaire, focusing on the intention to leave the occupation and emotional labor. The questionnaire was conducted from June to July 2022. Through this two-phase distribution method, after exclusion of invalid responses, a total of 288 valid responses were collected, resulting in a response rate of 96%. The proposed hypotheses were verified using hierarchical regression conducted with SPSS version 25.0. Results The findings indicated that nurses’ fear of COVID-19 was significantly and positively associated with their intention to leave the occupation and surface acting, but negatively associated with their deep acting. Moreover, the implementation of knowledge management significantly moderated the positive relationship among fear of COVID-19, intention to leave the occupation, and surface acting. A robust knowledge management system weakened the positive association among fear of COVID-19, intention to leave the occupation, and surface acting. Conclusion In summary, nurses’ fear of COVID-19 may increase their tendency to leave the nursing profession and engage in more surface acting and less deep acting. However, effective knowledge management practices can mitigate these adverse effects. Hospitals can thus establish and employ comprehensive knowledge management systems to enhance nurses’ resilience and help alleviate their fear of future pandemics and their potential negative repercussions.